ANALISIS KRITIS ATAS AHISTORISITAS PEMIKIRAN ARTHUR JEFFERY - Safri (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Study of religious texts will remain continuously evolve to infinite time. There was no denying the study of the Qur'an itself. Study of the Qur'an is not only done by Muslim scholars, but also take care of the other readers, including orientalis. With a wide range of interests, the Orientalists do indepth review of the Qur’an. Ranging from economic interests, politics, and religion. From a variety of interests, one of which became the subject orientalis is thought Arthur Jeffery. Australian-born character doing a lot of study on the Qur'an, so he did a variety of ways to find the weaknesses of the Qur’an. In his study, Arthur concluded that al-Fatiha is not part of the Qur'an, but just ordinary prayer. In addition, he also claims that there is a mystical verses are not meaningful in the Qur'an as al-muqatta'ah verses. For him the verses are just the initials of the friends who was instrumental in depositing the Qur'an in the time period of codification. In fact, he also entered the criticism of Muhammad's prophethood is filled with lies, and accusations stating that the language of the Qur’an is not original in terms of both writing and content. And various other criticisms. Based on the thoughts of Arthur, author focused on his premise about the position of al-Fatiha in the Qur'an and his claim to the mystical verses of the verses of almuqaththa'ah. In short, the author see Jeffrey mindset that is ahistorical, and only built on the assumption that too much influenced by his background as a scholar who was prepared as missionaries at the time.